2021
DOI: 10.14710/ik.ijms.26.1.37-44
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community structure and it’s relationships with water quality in Bangka Island, Indonesia

Abstract: Phytoplankton plays an important role in primary productivity in marine environment. Various environmental changes in coastal area will impact the water quality and their phytoplankton compositions. The purpose of this study is to examine the abundance of phytoplankton from two different sites, i.e Tanah Merah (close to mining site) and Semujur Island (away from mining site) in Bangka Island. Phytoplankton and water sample were collected on June- August 2018. Water quality was measured using water quality chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Concerning the condition of other biotic components, zooplankton abundance was directly proportional to phytoplankton, whereby the higher abundance was observed at stations 1 and 2 (more than 50,000 cells/m 3 ). This similar relationship was consistent with many studies (Grémillet et al, 2008;Purnamaningtyas & Mujiyanto, 2021;Wisha et al, 2018;Yusuf et al, 2021). In addition to larvae abundance, the pattern was not proportional at every station, whereby higher abundance was observed at stations 2 and 4, with more than 500 Ind/L, while a smaller value was found at stations 1 and 3, ranging from 83−351 Ind/L (Fig.…”
Section: Fisheries and Aquatic Sciencessupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning the condition of other biotic components, zooplankton abundance was directly proportional to phytoplankton, whereby the higher abundance was observed at stations 1 and 2 (more than 50,000 cells/m 3 ). This similar relationship was consistent with many studies (Grémillet et al, 2008;Purnamaningtyas & Mujiyanto, 2021;Wisha et al, 2018;Yusuf et al, 2021). In addition to larvae abundance, the pattern was not proportional at every station, whereby higher abundance was observed at stations 2 and 4, with more than 500 Ind/L, while a smaller value was found at stations 1 and 3, ranging from 83−351 Ind/L (Fig.…”
Section: Fisheries and Aquatic Sciencessupporting
confidence: 92%
“…The highest value was identified at station 1, and the lowest was found at station 4. Primary production is defined as the amount of organic compound synthesis from the atmosphere and aqueous CO 2 , where this process occurs during a photosynthesis mechanism performed by the autotroph biota and relies on nutrient availability (Yusuf et al, 2021). Hence, the primary productivity in every station was in line with the abundance of phytoplankton and chlorophyll-a.…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 99%
“…The total amount of observed phytoplankton in April was generally higher than September, with a deviation of about 712,000 and 694,975 cell/L for Bayeun and Lebuk Buni stations, respectively. The most abundant genera during the April survey were Chaetoceros (475,584 cells/L), Bacteriastrum (192,498 (Yusuf et al, 2021). Therefore, water quality assessment at the same observation station on the East Aceh coast is crucial to examining the most influential environmental parameters shaping phytoplankton abundance.…”
Section: The Abundance Of Phytoplanktonmentioning
confidence: 99%
“…Aside from direct surveys in water quality conditions, phytoplankton abundance is a biological parameter that can be a bio-indicator determining the pollution level (Villanoy et al, 2011). Phytoplankton is a marine autotroph biota that is imperative to support the food chain as the primary producer in the ocean (Yusuf et al, 2021). Meanwhile, phytoplankton is also sensitive to changes in water environmental conditions, whereby a slight degradation in water quality could impact the decrease of phytoplankton communities (Purnamaningtyas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of phytoplankton was used to determine the availability of natural food in water and determine the water quality of an ecosystem [16][17][18]. An investigation reported that the intestinal contents of P. uveae consisted of foraminifera, algae, mucus, and chyme [19].…”
Section: Introductionmentioning
confidence: 99%